Optimasi Kinerja Kombinasi Adsorben dalam Mereduksi Logam Besi dan Nikel Sampel Air - Edi Ilimu; Alimuddin; Sarniah (FKIP Universitas Palangka Raya, 2023)
Clean water or drinking water is one of the supporting materials for the survival of living things, especially humans, which should be free from heavy metal contamination and pose no risk to health. In an effort to reduce heavy metal levels in improving water quality through simple techniques and based on natural ingredients, the authors use jackfruit skin and natural zeolite as adsorbents. The purpose of this study was to determine the adsorption capacity of activated carbon from jackfruit skin combined with natural zeolite in reducing the concentration of iron (Fe) and nickel (Ni). The research was conducted on a laboratory scale using the method of varying the concentration of activated carbon which was analyzed using Atomic Absorption Spectrophotometry (AAS). The optimum adsorption power in reducing the concentration of Fe metal occurs in the x:y composition with the adsorbed concentration (mass of analyte) of 0.4083 ppm (0.1021 mg) for 60 minutes. Meanwhile, Ni metal was found in a combination of 2x:y composition dyes with the adsorbed concentration (mass of analyte) of 0.6017 ppm (0.1504 mg). The adsorption capacity of the adsorbent generally decreased with increasing mass of the dye packaged activated carbon adsorbent both in the analysis of Fe and Ni metal content.